Enhancing 3R Literacy through a Social Inclusion Library as a Holistic Solution for Community Empowerment at KUB IKREKS : Peningkatan Literasi 3R melalui Perpustakaan Inklusi Sosial sebagai Solusi Holistik Pemberdayaan Masyarakat di KUB IKREKS - Monika, Winda; Nasution, Arbi Haza; Ravelino, Parlindungan; Nur, Mutia; Kurniawan, Wahyu (Institut Riset dan Publikasi Indonesia, 2024)
This Community Service Program (PkM) aims to improve 3R literacy (Reduce, Reuse, Recycle) and information retrieval skills among members of the Ibu-Ibu Kreatif Kembang Setaman Joint Business Group (KUB IKREKS). The training emphasizes the importance of inclusive libraries as empowerment centers and sources of information. Three main topics were covered: inclusive libraries, environmental education, and waste management, as well as digital information retrieval related to environmental literacy. The evaluation results showed a significant increase in participants' understanding, measured through pre-test and post-test assessments. Understanding of access to digital libraries increased by 55%, while systematic information retrieval skills improved by 38.75%. In addition, the satisfaction questionnaire revealed a 97.14% satisfaction rate, with 98.57% of participants stating that the material was very useful. This activity successfully raised participants' awareness of the importance of better waste management and the role of inclusive libraries in supporting community and environmental empowerment.